Keberlanjutan Usahatani Kopi Robusta di Desa Twelagiri, Kecamatan Pagedongan, Kabupaten Banjarnegara - Ardina, Vinda Elza; Yuliawati (Universitas Veteran Bangun Nusantara, 2025)
Twelagiri Village, Pagedongan District, Banjarnegara Regency, is one of the main producers of Robusta coffee facing sustainability challenges across the economic, social, and ecological dimensions. This study aims to analyze the sustainability level of Robusta coffee farming in the KOPBASEL Farmer Group based on these three dimensions. The research was conducted from June to August 2022 using a quantitative approach. Primary data were collected through structured interviews with questionnaires, while secondary data were obtained from literature studies. A total of 25 members of the farmer group were selected as respondents using a census method. Sustainability analysis was carried out using the Multidimensional Scaling (MDS) method with the RAPFISH (Rapid Assessment Techniques for Fisheries) software, processed in Microsoft Excel. The results show that the sustainability index of Robusta coffee farming in Twelagiri Village is 58.61 for the economic dimension (fairly sustainable), 62.97 for the social dimension (fairly sustainable), and 79.36 for the ecological dimension (highly sustainable). The ecological dimension demonstrated the best result with a highly sustainable status, while the economic and social dimensions showed a fairly sustainable level. The sustainability of Robusta coffee farming is highly dependent on maintaining seed quality and proper fertilizer management, as well as the expansion of information and participation of farmer group members in extension activities.